Validity Test of Lean Healthcare using Lawshe’s Method - Azyyati Anuar; Daing Maruak Sadek (International Journal of Supply Chain Management, 2018)
ABSTRACT: The objective of this paper is to measure the validity of lean healthcare in the healthcare sector specifically in the Malaysias private hospitals. Validation of content is significantly important to ensure the development of questionnaires is an appropriate to measure the subject. Thus, content validity has been conducted to ensure the adapted instrument from the previous studies by using seven Subject Matter Expert (SME) to validate the instrument. Next, Lawshes method was consumed for the purpose to scale or measure the content validity of each item. From the result, it indicates the result has fulfilled the minimum criteria of Lawshes scale with more than half saying essential, denotes as an E compared to U useful but not essential and N not necessary. In conclusion, although it considered as classical measurement, but the Lawshes method still significant as one of the statistical method in quantitative study to determine the validity of each item.